Análisis de la recaudación tributaria por recursos determinados en la Municipalidad Provincial de Maynas, periodo 2018 – 2022 - Lopez Vizalote, Jhon Franco (2024)
Municipal tax revenues consist of a series of taxes that are in effect for a certain period of time and are managed by each municipality. The present investigation seeks to determine the tax collection for determined resources in the Provincial Municipality of Maynas, during the period 2018-2022, for which a descriptive analysis and non-experimental design was applied, consisting of six municipal taxes and a payment facility of debt. From the analysis carried out, it is determined that the collection presented interannual variations, with 2018 having the highest growth recorded with a variation of 42.94% compared to 2017, with total amounts collected of S/ 10,912,702.44 and 7,634,545.37 million respectively. Additionally, the first biennium (2018-2019) shows very slight growth of 0.58% compared to the last biennium (2021-2022), which showed a growth of 9.24%, with the average variation in total collection for the five-year period analyzed being positive. in S/ 10,368,925.61 million, that is, 11.00% per year. Likewise, the “Property Tax” concentrated the highest collection with an amount of S/ 40,954,547.92 million, which represents 78.99% of the total, followed by the “Alcabala Tax” for an amount of S/ 8,996,295.39 million, which represents the 17.35% of the total collected.